Proceedings physiotherapy in damage to the anterior cruciate ligament - Michalina Pawiłan; Krystian Kałużny; Anna Kałużna; Wojciech Hagner; Walery Zukow (Kazimierz Wielki University, 2017)
The knee joint is the largest joint of the human body. The specific construction, location and long lever of the knee joint make it one of the most frequently damaged joints in the human body. According to scientific reports, the anterior anterior cruciate ligament (ACL) is the most frequently damaged anatomical structure within the knee. As reported by Pritsch statistics from 2009 in Poland, an average of 3 thousand reconstruction of ACL annually. The paper presents related issues with damage to ACL. Preoperative treatment, choice of treatment method, conservative treatment and postoperative rehabilitation in ACL injury were presented.